2023
DOI: 10.1371/journal.pone.0272752
|View full text |Cite
|
Sign up to set email alerts
|

Assessing COVID-19 pandemic excess deaths in Brazil: Years 2020 and 2021

Abstract: We estimated the impact of the COVID-19 pandemic on mortality in Brazil for 2020 and 2021 years. We used mortality data (2015–2021) from the Brazilian Health Ministry for forecasting baseline deaths under non-pandemic conditions and to estimate all-cause excess deaths at the country level and stratified by sex, age, ethnicity and region of residence, from March 2020 to December 2021. We also considered the estimation of excess deaths due to specific causes. The estimated all-cause excess deaths were 187 842 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Likewise, there was excess suicide in at least one of the 4-month periods, regardless of gender, in the North, Southeast, and especially the Northeast regions, where 83.3% (55/30) more suicides than expected occurred among women 60 years old and older from July to October 2021. The 4-month period of July to October 2021 is closely situated with the 2 months following the great mortality peak due to COVID-19 in Brazil (Colonia et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, there was excess suicide in at least one of the 4-month periods, regardless of gender, in the North, Southeast, and especially the Northeast regions, where 83.3% (55/30) more suicides than expected occurred among women 60 years old and older from July to October 2021. The 4-month period of July to October 2021 is closely situated with the 2 months following the great mortality peak due to COVID-19 in Brazil (Colonia et al, 2023).…”
Section: Discussionmentioning
confidence: 90%
“…Data were obtained from the Mortality Information System (SIM) of the Brazilian Ministry of Health for the period of 2015 to 2022. Given Brazil’s vast regional inequities in COVID-19 outcomes [ 12 , 13 ], the country’s five macroregions (North, Northeast, Central-West, South, Southeast) were employed as units of analysis. The North and Northeast regions of the country are historically socioeconomically disadvantaged as compared to Brazil’s Southeast and South, the centers of Brazil’s industrial capacity and urbanization [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, studies have been recently reported showing that a reasonable estimate of excess mortality figures is also possible from only the age-specific prevalence and incidence data for a disease condition [13] . Excess mortality has therefore emerged as a valuable tool for estimating the impact of COVID-19 in various countries [14] , [15] , [16] , [17] , being extensively utilized in academic literature and presently as well as by World Health Organization (WHO) [18] . For 2020–21 WHO has estimated around 15 million excess deaths occurred globally [19] .…”
Section: Introductionmentioning
confidence: 99%